Feel good in the medical pharmacology - Bavane, Dattatray Sampatrao; Naikwadi, Akram (International Journal of Basic & Clinical Pharmacology, 2017)
Background: A curriculum is a vision and road map to meet academic objectivities. The major objectives of teaching pharmacology to the medical students is best way of understanding, retaining pharmacological information and to provide a rational basis for choosing drugs skilfully to relieve patient’s ailments. For better understanding of subjects and its correlation the sequential and interdependent schedule achieved through rearrangements of topics. So that earlier chapters of this pattern are arranged in such manner as general consideration of pharmacological principles and physiological topics of treatment part slowly in 3rd term. By the time student of IInd M.B.B.S are familiar with disease conditions from other paraclinical and clinical departments to achieve the goal for understanding of remaining topics. There should be continuous ongoing reforms for discovering, interpreting, revising and delivering the current knowledge of the subject relevant to the needs of society as a part of research. Methods: A structured 16 point questionnaire containing both open and close ended questions regarding reforms and innovation in pharmacology is prepared for opinion poll. The total 289 participant are from III, IV, V, VI, VII and VIII term’s M.B.B.S. students. The participants are also allowed to offer their own suggestions for certain important item regarding modification in teaching curricula of the subjects. Results: Large majority of the students of opinion poll are in favour of reforms and innovations. They also suggested their own suggestions regarding the refreshing of the subjects. Conclusions: The teaching program of pharmacology at regular interval should be researched to discover, interpret, revise and deliver the updates in basic pharmacological knowledge of drugs and its application.